Automatic occupation identification of Twitter users using graph neural network - Li, Jiaheng (Nanyang Technological University, 2023)
With the advent of the digital age, the Internet has gradually become an integral part of people's lives. The emergence and development of the Internet have significantly improved people's lives, and information can be spread to all parts of the world in a very short period of time through the Internet. So, people can communicate with each other across distances and sit at home and understand what's happening worldwide. As one of the most popular online social platforms in the world, Twitter has brought great convenience to the Internet for people to transmit information. People can tweet about what's happening around them, find out what's happening in other parts of the world, find the articles and information they want, and more. Thus, Twitter also facilitates the democratization of scholarly articles. More and more users are now publishing academic articles on Twitter because they want to share their research results, want to have discussions on Twitter with practitioners in related fields covered by others, and want to share cutting-edge research results. Both researchers and the public have seen Twitter as a search platform for scholarly articles. Slowly, more and more researchers have discovered that they can use Twitter to investigate and analyze what academic fields are more interesting to the public. In this article, we build a classifier that helps researchers in such analytical studies.